F'(-2)=-12

f'(3)=-1

y=2x+4, f'(-1)=2​

LLA7A LLA7A    2   28.01.2021 06:05    0

Ответы
PoMOgiTe212lk PoMOgiTe212lk  27.02.2021 06:12

ответ:1

1)f`(x)=3x²-2x-1=0

D=4+12=16

x1=(2-4)/6=-1/3

x2=(2+4)/6=1

 +                    _                   +

(-1/3)(1)

         max               min

ymax=-1/27-1/9+1/3+2=(-1-3+9+54)/27=59/27

ymin=1-1-1+2=1

2)f`(x)=-7e^x+(8-7x)e^x=e^x*(-7+8-7x)=0

1-7x=0

x=1/7

 +                           _

(1/7)

                max

ymax=(8-1)*e^(1/7)=e^(1/7)

2

f`(x)=3x²-2x-1=0

D=4+12=16

x1=(2-4)/6=-1/3

x2=(2+4)/6=1

 +                    _                   +

(-1/3)(1)

возр           убыв            возр

3  

смотреть 1

x=-1/3∈[-1;3/2]

x=1∈[-1;3/2]

y(-1)=-1-1+1+2=1

y(-1/3)=59/27 наиб

4

y(1)=1

y(3/2)=27/8-9/4-3/2+2=(27-27-12+16)/8=1/2 наим

5

f`(x)=3x²-2x-1

f``(x)=6x-2 прямая проходит через точки (0:-2) и (1;4)

Объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра